2019
DOI: 10.1094/phyto-04-19-0115-r
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Screens Reveal Novel Haustorium Inhibitors in the Root Parasitic Plant Triphysaria versicolor

Abstract: Root parasitic weeds in Orobanchaceae pose a tremendous threat to agriculture worldwide. We used an in vitro assay to screen libraries of small molecules for those capable of inhibiting or enhancing haustorium development in the parasitic plant Triphysaria versicolor. Several redox-modifying molecules and one structural analog of 2,6-dimethoxybenzoquine (DMBQ) inhibited haustorium development in the presence of the haustorium-inducing factor DMBQ, some of these without apparent growth inhibition to the root. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The process of haustorium development was reported to be more sensitive to cellular redox states than root growth [38], but in broomrape we found that the reduction in radicle growth was induced at lower benzoquinone concentrations than those concentrations active for haustorium induction. It has been debated whether the growth cessation is necessary for haustorium functioning, or if it is the consequence of a reduction in resources required for root growth [31].…”
Section: Induction Of Haustoriummentioning
confidence: 51%
“…The process of haustorium development was reported to be more sensitive to cellular redox states than root growth [38], but in broomrape we found that the reduction in radicle growth was induced at lower benzoquinone concentrations than those concentrations active for haustorium induction. It has been debated whether the growth cessation is necessary for haustorium functioning, or if it is the consequence of a reduction in resources required for root growth [31].…”
Section: Induction Of Haustoriummentioning
confidence: 51%
“…DMBQ did not induce visible signs of toxicity in P. ramosa as has been observed in other parasitic weeds which have been described as turning brown and die at concentrations higher than 50 µM [52,61]. Unlike more hydrophobic quinones, DMBQ is sufficiently soluble in water to make fresh working stocks at 1 mM directly in water, without the solvent DMSO usually used in labs to make stock solutions for haustorial induction assays of Phelipanche, Striga, and Triphysaria [49,65,66]. The effect of quercetin was evaluated at concentration range of 100 µM and 5 µM (Figure 4B,G).…”
Section: Resultsmentioning
confidence: 66%
“…Also, chemically inhibiting peroxidase activity, and thus altering the redox homeostasis, reduces haustorium formation in Striga spp. and Triphysaria (Wada et al ., 2019; Wang et al ., 2019). The expression of a superoxide dismutase in P. japonicum intrusive cells further supports a role for redox regulating enzymes in haustorium development.…”
Section: Discussionmentioning
confidence: 99%